Toward enhancing the photoelectrochemical water splitting efficiency of organic acid doped polyaniline-WO3 photoanode by photo-assisted electrochemically reduced graphene oxide - Hosseini, Mir Ghasem; Sefidi, Pariya Yardani; Aydin, Zeynep; Kinayyigit, Solen (Pergamon-Elsevier Science Ltd, 2020)
In this research, the camphor sulfonic acid doped polyaniline-WO3 (CSA PANI-WO3) nanocomposite was modified with rGO. The semi conductive nature of CSA PANI-WO3 was used for in situ photoelectrochemical reduction of GO to rGO. The morphology, structure, and chemical composition of CSA PANI-WO3-rGO were evaluated by Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS) and Transmission electron microscopy (TEM). The influence of rGO addition on the solar photoelectrochemical (PEC) water splitting performance of CSA PANI-WO3 toward water oxidation was investigated. The maximum photocurrent density of 1.54 mA/cm(2) (at 1.23 V vs. reversible hydrogen electrode (RHE)) was achieved for CSA PANI-WO3-rGO photoelectrocatalyst which was 2.41, 4.05, and 8.11 times higher than those of CSA PANI-WO3 (0.64 mA/cm(2)), pure CSA PANI (0.38 mA/cm(2)), and pristine WO3 (0.19 mA/cm(2)), respectively. Also, the applied bias photon-to-current efficiency (eta) of CSA PANI-WO3- rGO was obtained 0.29% which showed fourteen - fold (0.02%), ten-fold (0.03%) and four-fold (0.07%) enhancements compared to the WO3, CSA PANI, and CSA PANI-WO3, respectively. The electrochemical impedance spectroscopy, as well as the Mott-Schottky results, confirmed the improvement in the photoelectrocatalytic performance of CSA PANI-WO3-rGO in comparison with other electrodes. The observed improvement in the PEC photoconversion efficiency of the CSA PANI-WO3 in the presence of rGO is due to the easier and faster interfacial charge separation and transferring. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: WO3; Polyaniline; Camphor sulfonic acid; Photo reduced graphene oxide; Water splitting